REFRACTORY HYPOTHYROIDISM TO LEVOTHYROXINE TREATMENT: FIVE CASES OF PSEUDOMALABSORPTION - YAVUZ, DİLEK; ELBASAN, ONUR (EDITURA ACAD ROMANE, 2022)
Context. A persistently elevated thyroid stimulating hormone (TSH) level is a common clinical problem in primary hypothyroidism patients treated with levothyroxine (LT4). Pseudomalabsorption, which is characterized by poor adherence,should be considered in cases of refractory hypothyroidism after excluding other causes, such as malabsorption. Objective. We reviewed the features of the patients with persistently elevated TSH despite high-dose LT4 therapy. Design. Symptom evaluation, medications, comorbid diseases and physical examination features of five patients who applied to our outpatient clinic between 20162019 and diagnosed with LT4 pseudomalabsorption were retrospectively analyzed. Subjects and methods. The LT4 loading test was performed with an oral dose of 1,000 mu g LT4. Demographic parameters, BMI, thyroid function tests, laboratory parameters for malabsorption were recorded. Results. We observed at least two-fold increase of free thyroxine levels during the test, which was considered pseudomalabsorption. Euthyroidism was achieved in two patients by increasing the LT4 dosage and in one patient with a change in the preparation. TSH decreased significantly after being informed about compliance in one patient. Another one was given LT4 twice weekly, but TSH remained elevated because of nonadherence. Conclusion. The LT4 loading/absorption test is a valuable tool to confirm the diagnosis of pseudomalabsorption. Informing patients, changing the preparation, increasing the dose, supervised intake of daily/weekly LT4 forms are treatment options for managing these cases.
Keywords: levothyroxine; pseudomalabsorption; refractory hypothyroidism; FACTITIOUS DISORDER; MALABSORPTION; ABSORPTION; GUIDELINES; DIAGNOSIS; PATIENT